The First Mrs. Rochester: Wrongful Confinement, Social Redundancy, and Commitment to the Private Asylum, 1883‑1923 - Warsh, Cheryl (Historical Papers / Communications historiques, 1988)
AbstractHistorians have debated the growth of asylums as either a movement towards socialcontrol or as a benevolent reform; yet commitment was primarily initiated by kin. Therapid overcrowding of asylums reflected the success of institutions in responding tofamily crises. Through analysis of 1,134 case histories of a private asylum, theHomewood Retreat of Guelph, Ontario, the dynamics of the late Victorian andEdwardian middle-class household are evident in the circumstances which culminated inthe decision to commit. Urban industrialization and the declining birth rate renderedhouseholds less able to care for the insane, while the permeation of capitalist relationsinto family life rendered the heads of households less willing to care for nonproductiveadult members, particularly socially redundant women. The diagnosis of neurastheniaenabled members of the middle class to institutionalize kin for behaviour which,although not violent or destructive, was irritating and antagonistic, thereby reflecting thehigh standard of middle-class proprieties.